(untitled) (Journal of Forest and Livelihood, 2003)
Forest User Groups (FUGs) in Nepal have become established as permanent grassroots local institutions. The most dynamic FUGs illustrate the remarkable achievements that are possible: beyond successfully protecting and managing their forest resources they are also assuming a co-ordinating role for wider community development. However many are constrained by inadequate institutional processes, compounded by weak and poorly coordinated support from external agencies. One way to address these constraints has been developed: a micro-level action planning process, which has been piloted across 11 FUGs. This involves self-assessment by FUGs on the basis of process indicators, decision-making through hamlet-level discussion, and improved participation of marginalized groups in decision-making, and has proved to be an effective basis for targeted demand-led support.